Evaluación del potencial de biomasa residual del ganado porcino para el aprovecham iento energético en la granja porcina García en el cantón La Maná barrio Miraflores sector El Toquillal en el año 2016. Diseño de un biodigestor alternativo para este propósito. - Villacrés Jirón, Mauricio Adrián (2016)
In this paper, the tools of Total Management Technology Efficient Energy for an energy characterization of Swine Farm Garcia apply. The potential of biomass were evaluated and the technological parameters of a digester is obtained from pig excrement present. An experimental installation of a type "Batch" digester own resources that allowed the characterization of the anaerobic digestion process, the substrate temperature, type of substrate (nutrients available), the volumetric loading, hydraulic retention time and level was constructed acidity (pH). By calorimetric experimental method it was determined that the caloric power of the biogas produced by the digester prototype is 5713 kcal / m3 , for a gas containing 61.2% methane particles. The financial evaluation confirmed the economic viability of the project because the NPV obtained a value of $ 26 041,47 for an IRR of 41%. In addition, the implementation of the proposed digester will save $ 1506.6 to the farm, leaving combust around 1,215 kg of liquefied petroleum gas. This will favor the environment, because they would be leaving emitted into the atmosphere 4.2 tons of CO2 per year.